2012
DOI: 10.1093/bja/aer330
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of sugammadex and neostigmine for reversal of rocuronium-induced muscle relaxation in morbidly obese undergoing general anaesthesia

Abstract: Administration of sugammadex provides fast recovery of neuromuscular function and prevents PORC in the morbidly obese, however neostigmine does not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(92 citation statements)
references
References 14 publications
2
83
1
6
Order By: Relevance
“…Morbidly obese patients are prone to postoperative respiratory complications, including hypoventilation, hypoxaemia, hypercarbia and airway obstruction [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morbidly obese patients are prone to postoperative respiratory complications, including hypoventilation, hypoxaemia, hypercarbia and airway obstruction [8].…”
Section: Discussionmentioning
confidence: 99%
“…The time to reach a train-of-four ratio (TOFR) ≥ 90% was 13 minutes with 50 μg/kg neostigmine and only 1.7 minutes with 2 mg/kg sugammadex [8]. It follows that sugammadex may be better at preventing the occurrence of residual curarization and possibly postoperative respiratory complication when compared to neostigmine.…”
Section: Introductionmentioning
confidence: 99%
“…Gaszynski et al studied reversal of rocuroniuminduced neuromuscular block with sugammadex 2 mgÁkg -1 corrected body weight or neostigmine 50 lg corrected body weight in 70 morbidly obese patients. 116 They showed that the time to achieve 90% train-of-four (TOF) ratio was significantly shorter in the sugammadex group than the neostigmine group at 2.7 vs 9.6 min, respectively (P \ 0.05), and the TOF ratio in the PACU was 109.8% in the sugammadex group vs 85.5% in the neostigmine group (P \ 0.05). Care should be taken to understand the dosing weight used when reading studies in this area.…”
Section: Postoperative Managementmentioning
confidence: 99%
“…This patient had both restrictive and obstructive pulmonary disease, and the deep neuromuscular block should be reversed adequately. Therefore, we administered the recommended dose of sugammadex to obtain prompt recovery of the neuromuscular function 6 . Sugammadex does not cause increase in bronchial secretions, which was very important in a patient with copious secretions.…”
Section: Discussionmentioning
confidence: 99%